2003
DOI: 10.1046/j.1365-2966.2003.07040.x
|View full text |Cite
|
Sign up to set email alerts
|

The Birmingham-CfA cluster scaling project - II. Mass composition and distribution

Abstract: We investigate the spatial distribution of the baryonic and non‐baryonic mass components in a sample of 66 virialized systems. We have used X‐ray measurements to determine the deprojected temperature and density structure of the intergalactic medium and have employed these to map the underlying gravitational potential. In addition, we have measured the deprojected spatial distribution of galaxy luminosity for a subset of this sample, spanning over two decades in mass. With this combined X‐ray/optical study, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
3

Year Published

2004
2004
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 74 publications
7
56
3
Order By: Relevance
“…9 the K band M/L ratio for the three clusters is compared to previous determinations at lower redshifts (Carlberg et al 1997;Cirimele et al 1997;Girardi et al 2000;Hradecky et al 2000;Rines et al 2001;Hoekstra et al 2002;Kneib et al 2003;Lin et al 2003;Sanderson & Ponman 2003;Andernach et al 2004;Gavazzi et al 2004;Rines et al 2004).…”
Section: Mass To Light Ratiosmentioning
confidence: 99%
See 3 more Smart Citations
“…9 the K band M/L ratio for the three clusters is compared to previous determinations at lower redshifts (Carlberg et al 1997;Cirimele et al 1997;Girardi et al 2000;Hradecky et al 2000;Rines et al 2001;Hoekstra et al 2002;Kneib et al 2003;Lin et al 2003;Sanderson & Ponman 2003;Andernach et al 2004;Gavazzi et al 2004;Rines et al 2004).…”
Section: Mass To Light Ratiosmentioning
confidence: 99%
“…Keeping in mind these issues that complicate the comparison of inhomogeneous samples, as well as possible systematic differences in the masses estimated by different means (see for instance Sanderson & Ponman 2003;Andernach et al 2004), we can compare the M/L ratio of the clusters studied in this work with estimates at lower redshift. A comparison of the cluster M/L ratios in the B band, out to redshift z 0.8, was presented for instance by Hoekstra et al (2002), who found that the evolution of the M/L ratio is consistent with the luminosity evolution of galaxies as derived from the fundamental plane in distant clusters (see their Fig.…”
Section: Mass To Light Ratiosmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 1 The halo-mass dependence of M/L is still not a fully resolved issue: While some dynamical studies indicate that mass increases faster than luminosity (Girardi et al 2002), such a trend is not seen from a recent X-ray based study (Sanderson & Ponman 2003). We note that since our clusters only cover a modest range in mass, our results must be combined with other data sets probing less massive systems to be able to address this issue.…”
Section: Results For M/lmentioning
confidence: 90%